Remembering Asia's World War Two - Frost, Mark Ravinder; Schumacher, Daniel; Vickers, Edward 1971- (Remembering the modern world, 2019)
Over the past four decades, East and Southeast Asia have seen a proliferation of heritage sites and remembrance practices which commemorate the region's bloody conflicts of the period 1931-45. Remembering Asia's World War Two examines the origins, dynamics and repercussions of this regional war 'memory boom.' Focusing on non-textual vehicles for public commemoration and considering both the local and international dimensions of war commemoration within the area, Remembering Asia's World War Two is ideal for students and scholars of Asian history, Asian studies, memory studies and heritage studies.